Outer Macular Microvascular Supply in Retinitis Pigmentosa Examined using Optical Coherence Tomography Angiography. (21st December 2021) - Hong, Mingsheng; Wen, Jiquan; Lou, Jixian; Xu, Jiehui; Xu, Tingjun
Abstract : Purpose . To determine the vessel density of the superior (SCP) and deep retinal capillary plexuses (DCP) in patients with retinitis pigmentosa (RP) using optical coherence tomography angiography (OCTA). Methods . This was a cross-sectional study. A total of 25 eyes of 25 healthy volunteers and 30 eyes of 17 patients with RP were evaluated in this study. The integrity of the ellipsoid zone in the macular fovea was evaluated as an intact or defect using a spectral-domain OCT. Commercial spectral domain coherence tomography angiography (OCTA) was used to scan the macular region of approximately 3 × 3 mm 2 . The vessel density in the SCP and DCP were calculated after appropriate layer segmentation and removal of projection artifacts. The central retinal thickness (CRT) was measured with automated software. The vessel densities in the SCP and DCP were compared between different groups using SPSS. Results . A total of 25 eyes of 25 healthy subjects and 30 eyes of 17 patients with RP were evaluated in the study. There was no significant difference in ages between the two groups ( F  = 0.065 and P = 0.937 ). There was a significant difference in SCP and DCP between the patients with RP and healthy individuals (P < 0.001 and P < 0.001 ). The DCP was significantly reduced in the parafovea region between the macular intact and defect groups P < 0.05, except in the fovea and nasal regions. After linear regression, the DCP/SCP ratio in the whole, fovea, and parafovea regions was closely related to the DCP vessel density P < 0.05, and CRT in the fovea and parafovea was not related to the whole DCP (P = 0.186 and P = 0.539 ). Conclusion . The vessel density decreased in patients with RP, especially in the DCP of the parafovea region. A greater loss of capillaries in the DCP was found when the macular region was involved. The DCP/SCP ratio may be an important indicator of RP.